COMPARISON OF GAUSSIAN HEAT FLOW OF FSW RELYING ON VON MISES CRITERION AND CONSTITUTIVE MODELS OF YIELD STRENGTH - Abdul Ridha , Ghassan Shaker; Abbas, Mohammed Abdulridha; Hashemi, Ramin; Lajis, Mohd Amri; Ahmed, Muhannad (Journal of Applied Engineering Science, 2025)
In the Friction Stir Welding (FSW) operation, the role of thermal applied load modeling is no secret to simulate the heat distribution produced from this process. Unfortunately, this modeling implemented in transient mode did not present an accurate model for the moving heat source resulting from FSW operation. The main reason for this issue is attributed to the confidence and deviation ratios, especially with the Gaussian Distribution (GD). Besides, the models adopted in this modeling did not utilize the constitutive models of yield strength for comparison. Accordingly, the current study aims to use GD with 99.75% and 0.25% ratios for confidence and deviation, respectively, in this thermal load. It also employed the Von Mises criterion with Voce, Hollomon, and Swift for this comparison as constitutive models. Accordingly, the hybrid models of the thermal load of FSW represented by Von Mises-Voce, Von Mises-Hollomon, and Von Mises-Swift have been adopted in the present study. These hybrid models were used with finite element simulation to validate the experimental thermal history of FSW for Al 6061-T6 under 800 rpm, 10 mm/min, and 15 kN for rotational speed, linear velocity, and applied force sequentially. Finally, this validation has proved the dominance of the Von Mises-Voce model for thermal history compared to other hybrid models. Moreover, this dominant model has also investigated the peak temperature with a 2.54% error ratio over the other hybrid models of thermal applied load in FSW.